2022
DOI: 10.1136/bmjgh-2022-009098
|View full text |Cite
|
Sign up to set email alerts
|

Community-based doulas for migrant and refugee women: a mixed-method systematic review and narrative synthesis

Abstract: BackgroundCommunity-based doulas share the same cultural, linguistic, ethnic backgrounds or social experiences as the women they support. Community-based doulas may be able to bridge gaps for migrant and refugee women in maternity settings in high-income countries (HICs). The aim of this review was to explore key stakeholders’ perceptions and experiences of community-based doula programmes for migrant and refugee women during labour and birth in HICs, and identify factors affecting implementation and sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Afulani and colleagues (2018) found similar results: women who were literate, wealthy, and employed were more likely to benefit from labour companionship [25]. These inequities in who receives support from a labour companion have also led to the development of critical programmes to support socially marginalised women, for example via community-based doula support for Indigenous women in Canada [88], Black and Latinx women in New York [89], and women from migrant and refugee backgrounds in Australia and the United Kingdom [90,91]. Only 28.6% of studies included in the scoping review reported that women were allowed to choose their companion.…”
Section: Discussionmentioning
confidence: 95%
“…Afulani and colleagues (2018) found similar results: women who were literate, wealthy, and employed were more likely to benefit from labour companionship [25]. These inequities in who receives support from a labour companion have also led to the development of critical programmes to support socially marginalised women, for example via community-based doula support for Indigenous women in Canada [88], Black and Latinx women in New York [89], and women from migrant and refugee backgrounds in Australia and the United Kingdom [90,91]. Only 28.6% of studies included in the scoping review reported that women were allowed to choose their companion.…”
Section: Discussionmentioning
confidence: 95%
“…In general, IRC has prioritized respectful care in this setting through refresher trainings, supportive supervision, coaching and mentoring, which have also shown some success elsewhere [ 30 ]. Integrating the refugee providers into the maternity team may contribute to better care for women as they are from the community, and also fill a complementary role with training to support and reduce the burden on the midwives, similar to on-call birth companions piloted in Tanzania or community-based doulas for refugees in high income countries [ 48 , 49 ]. However, refugee providers in particular mentioned feeling overworked while also seeing their compensation reduced resulting in their feeling undervalued, similar to findings elsewhere [ 30 ].…”
Section: Discussionmentioning
confidence: 99%